Is late-preterm birth a risk factor for hypertension in childhood? - ALPAY, HARİKA; GÖKCE, İBRAHİM; BİLGEN, HÜLYA SELVA (SPRINGER, 2014)
Late-preterm birth is associated with higher rates of neonatal morbidity and mortality and higher health care utilization, but its impact on later life is not well known. In this study, we aimed to evaluate whether late-preterm birth affects blood pressure, renal function, and urinary protein excretion in children later in life. Sixty-five children aged 4 to 13 years born as late-preterm and 65 age- and sex-matched children born full term were evaluated with 24-h ambulatory blood pressure monitoring (ABPM), urinary microalbumin excretion (UAE), and glomerular filtration rate (GFR). All subjects underwent ABPM prospectively. For each gender, daytime, nighttime, and 24-h systolic and diastolic and mean blood pressures (SBP, DBP, and MAP) were transformed to standard deviation scores (SDS). Blood pressure profiles (SBP DBP, and MAP) were considered abnormal when the corresponding SDS values exceeded 1.63. Urinary microalbumin excretion was expressed as milligrams per day, and the value between 30 and 300 mg/day was defined as microalbuminuria (MA). There was no significant difference in the mean GFR and MA levels between late-preterm and term children. 24-h systolic BP SDS, daytime systolic BP SDS, nighttime systolic BP SDS, 24-h diastolic BP SDS, nighttime diastolic BP SDS, 24-h MAP BP SDS, daytime MAP BP SDS, and nighttime MAP BP SDS were found to be significantly higher in late-preterm children compared to term children. Conclusion: We conclude that late-preterm children have higher BP levels, so those children should be followed up carefully by the pediatrician regarding probable hypertension in their future life.
Keywords: Late preterm; Ambulatory blood pressure monitoring; Hypertension; Microalbuminuria; Glomerular filtration rate; AMBULATORY BLOOD-PRESSURE; INTRAUTERINE GROWTH RESTRICTION; GESTATIONAL-AGE; RENAL-FUNCTION; CARDIOVASCULAR-DISEASE; BORN PRETERM; FOLLOW-UP; WEIGHT; CHILDREN; INFANTS